Perbuatan Melawan Hukum Oleh Kreditur Dalam Eksekusi Objek Jaminan Fidusia - Aprilian Saputra; Mardalena Hanifah (UIR Press, 2024)
This study aims to determine the occurrence of unlawful acts by creditors in the execution of fiduciary guarantees. The research method used is sociological legal research method. This research is descriptive analytical which provides an explanation of the description of the circumstances and conditions regarding Unlawful Acts by Creditors in the Execution of Fiduciary Guarantee Objects. Data collection by means of interviews, and literature study. Data analysis used is qualitative analysis. The actions of the creditor who continues to withdraw the fiduciary security object even though the debtor objects to voluntarily surrendering the fiduciary security object are unlawful because they are contrary to the rights of the debtor and the decision of the Constitutional Court Number 18/PUU-XVII/2019. The debtor suffers a loss where the debtor loses the right to control the object of fiduciary guarantee. The creditor must be held accountable for his actions by providing compensation to the debtor in accordance with Article 1365 of the Civil Code